Pyrrhonian Buddhism: a philosophical reconstruction - Kuzminski, Adrian (Routledge Taylor & Francis Group, 2021)
Preface -- 1. West Meets East -- 2. Diogenes Laertius -- 3. Sextus Empiricus -- 4. Timon and Aulus Gellius -- 5. Pragmata and Dependent Origination -- 6. Emptiness and the Suspension of Belief -- 7. Ataraxia and Bodhi -- Bibliography -- Index.